Death and Dementia: A Further Look At the Complex Relationship Set in Madison v. Alabama - Darren Frankel (Washington University Undergraduate Law Review, 2024)
When creating a judicial precedent, accuracy and precision matter. However, modern science, although evolving, is not perfect. The rational understanding doctrine states that for the death penalty to be applicable, one must have a rational understanding of their crimes and reason for execution. In Madison v. Alabama (2019), Appellant Vernon Madison was charged with capital murder and was set to receive the death penalty before suffering a series of severe strokes. Diagnosed with vascular dementia, attendant disorientation, cognitive impairment, and memory loss as a result of these strokes, Madison’s legal team was granted certiorari before the Supreme Court. Despite no foolproof test for dementia, the Court accepted conflicting expert opinions debating whether Madison truly had dementia. This is where I found flaws in the reasoning of Madison. The Court’s reliance on medical diagnoses with less than 100% accurate results opens the door to future manipulation. The sweeping rational understanding doctrine can provide justice to victims across the nation, but at the same time, it can be manipulated to protect convicted criminals. With more research being conducted discussing ‘pseudodementia,’ dementia-like symptoms but not the same as dementia, and other possible explanations for dementia-like symptoms, this article asserts that the rational understanding doctrine is too broad to apply to capital punishment. Therefore, the Court appears to have two options: to either continue hyper-refining 8th Amendment capital punishment eligibility or remove themselves from the complexity of capital punishment. Without completely accurate fool-proof science, the Court runs the risk of allowing those sentenced to death to escape culpability via insanity defenses.
Keywords: Death Penalty; 8th Amendment; Alabama; Insanity Defense